2017
DOI: 10.1038/srep40296
|View full text |Cite
|
Sign up to set email alerts
|

Newborn chicks show inherited variability in early social predispositions for hen-like stimuli

Abstract: Predispositions of newborn vertebrates to preferentially attend to living beings and learn about them are pervasive. Their disturbance (e.g. in neonates at risk for autism), may compromise the proper development of a social brain. The genetic bases of such predispositions are unknown. We use the well-known visual preferences of newly-hatched chicks (Gallus gallus) for the head/neck region of the hen to investigate the presence of segregating variation in the predispositions to approach a stuffed hen vs. a scra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 48 publications
5
52
0
Order By: Relevance
“…Fertilized eggs of three breeds of domestic fowl (Gallus gallus) kept genetically isolated for 20 years in the conservation programme CO.VA 33,34 were obtained from the Agricultural High School "Duca degli Abruzzi", Padova (Italy). Further details on this population, breeds and their early predisposition are available in previous publications 6,35 . Eggs were incubated in darkness at a constant temperature of 37.7 °C, humidity 40% until 3 days before hatching (day 17 of incubation).…”
Section: Subjects and Rearing Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fertilized eggs of three breeds of domestic fowl (Gallus gallus) kept genetically isolated for 20 years in the conservation programme CO.VA 33,34 were obtained from the Agricultural High School "Duca degli Abruzzi", Padova (Italy). Further details on this population, breeds and their early predisposition are available in previous publications 6,35 . Eggs were incubated in darkness at a constant temperature of 37.7 °C, humidity 40% until 3 days before hatching (day 17 of incubation).…”
Section: Subjects and Rearing Conditionsmentioning
confidence: 99%
“…The preference for speed changes has been described as a predisposition to attend to 2 "animacy" cues, the properties associated with living beings 3,4 . Other animacy cues that are attractive for neonates include face-like stimuli [4][5][6][7][8][9] , biological motion 10,11 and self-propulsion 12 . The initial orienting response towards animate objects, in turn, enhances learning and social interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative research on human infants and newly-hatched domestic chicks (Gallus gallus) found striking similarities in the static and dynamic visual cues that attract their attention soon after birth (Di Giorgio et al, 2017). Among static cues, a predisposition to approach a stuffed hen over a scrambled version of the same stimulus has been consistently observed in visually-naïve chicks (Bolhuis and Horn, 1997;Johnson and Horn, 1988;Mayer et al, 2016;Versace et al, 2017). This preferential approach is driven by the configuration of features present in the intact head and neck (Johnson and Horn, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…representing inherited genetic variability (17), and meaning that genetic content is capable to explain (at least partially) an individual's behavioral (in)variability. At the cellular level, neuronal correlated variability for spikes and subjects' performance displays the same relationship as learning and attention (18), perhaps through the affected impulsivity (as shown in this study).…”
Section: Introductionmentioning
confidence: 99%